O uso do celular como dispositivo no processo ensino-aprendizagem: um estudo sobre bullying a partir das averiguações nas histórias em quadrinhos - Moreira, Cledenilson Valdevino (2021)
The present study comprised pedagogical activities aimed to the learning of the eighth grade students in a public school located in Pedro Velho-RN, in a virtual way, through remote classes in the face of Covid – 19 pandemic that spread throughout the world and reached Brazil. In the context of the contemporary world, when the realization of remote activities, using a cell phone, it’s relevant that the school enable students meaningful learning, through comic books, reading and the use of digital technological instruments. The general objective of the study has consisted of understanding how the cell phone has contributed to the students reading, using textual and discourse genres, comic books, as a support study about fighting bullying. As specific objectives, has enhanced the students learning, given the importance of reading comic books, targeted actions against bullying, in a school and in a social context; understanding how comic books contribute to combat acts of bullying, comparisons of students views about it, produce a podcast on a cell phone, through readings and discussions during the study. According to theoretical assumptions like Marcuschi (2008), Antunes (2012), Arantes (2015) Bakhtin (2003), Fante (2012), Vergueiro (2004), among others. The applied methodological procedures understanding an action research of interventionist nature, text reading, participation, and a documental research, circle conversation and pedagogical workshop. These study instruments made it possible to carry out the study with students. The use of cell phone was fundamental. Students researched about HQs; and others directed by the teacher-researcher, activities how to study using a cell phone, to combat bullying, and finally the collective podcast production. The results were satisfactory with the improvement of students reading, with more knowledge assimilation about bullying combat at school and family, more dynamic learning about reading and the new search procedure and reading through pedagogical use of contemporary digital tools, this way, a meaningful learning for all participants.